Blue Economy Village: Model Kemitraan Berbasis ACTORS Dalam Pemberdayaan Ekonomi Desa Maritim Di Kabupaten Nagan Raya - Macella, Agatha Debby Reiza; Sari, Rahmi Indah; Saputra, Ilham Mirza; Latif, Ikhwan Rahmatika (Department of Public Administration, Muhammadiyah University of Makassar, 2025)
This Study aims to analyze the effectiveness of the ACTORS theory based partnership model in economic empowerment in maritime villages in Nagan Raya Regency.The research method used is a qualitative method with a descriptive approach through in depth interviews, observation, and documentation, and data validation using source triangulation and member check. The results showed that the confidence & competence and authority indicators obtained the lowest scores (2 out of 5 each), indicating low confidence, technical skills, and limited village authority in program implementation. In contrast, the responsibility indicator received the highest score (4 out of 5), which is due to the implementation of a digital financial governance system (siskeudes) that can improve accountability. These findings indicate the need to increase human resource capacity and strengthen local institutions to optimize the blue economy concept in a sustainable manner in coastal areas.